COMMONALITY OF LANGUAGE AND CULTURE - Qalandarov Shuxratjon (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In this article, an analysis of the opinions of scientists on the formation, development and functionality of the common language and culture has taken place.